Screening for Cognitive Function in Complete Immobility Using Brain–Machine Interfaces: A Proof of Principle Study - Lulé, Dorothée; Hörner, Katharina; Vazquez, Cynthia; Aho-Özhan, Helena; Keller, Jürgen; Gorges, Martin; Uttner, Ingo; Ludolph, Albert C. (Frontiers in Neuroscience, 2018)
Background: In many neurological conditions, there is a combination of decline in physical function and cognitive abilities. For far advanced stages of physical disability where speaking and hand motor abilities are severely impaired, there is a lack of standardized approach to screen for cognitive profile. Methods:N = 40 healthy subjects were included in the study. For proof of principle, N = 6 ALS patients were additionally measured. For cognitive screening, we used the Edinburgh cognitive and behavioral ALS screen (ECAS) in the standard paper-and-pencil version. Additionally, we adapted the ECAS to a brain–machine interface (BMI) control module to screen for cognition in severely advanced patients. Results: There was a high congruency between BMI version and the paper-and-pencil version of the ECAS. Sensitivity and specificity of the ECAS-BMI were mostly high whereas stress and weariness for the patient were low. Discussion/Conclusion: We hereby present evidence that adaptation of a standardized neuropsychological test for BMI control is feasible. BMI driven neuropsychological test provides congruent results compared to standardized tests with a good specificity and sensitivity but low patient load.